HUBUNGAN TINGKAT PENGETAHUAN DAN AKSES INFORMASI IBU DENGAN PEMBERIAN KAPSUL VITAMIN A PADA BALITA - Mutiara, Sherly; Nurshal, Rezki Amalia; Asriani, Dwi Suci; Zaky, Abdul (Journal of Hospital Administration and Management (JHAM), 2024)
Vitamin A is the most essential nutrition, it isbecause ourfood consumption is insuficient and still low, so it must be fulfilled from the outside. Lacking of Vitamin A(KVA) increases pain and death, is prone to infectious diseases such as diarrhea, pneumonia, andeventually death. The purpose of this study is to find out the relationship between mother's level of knowledge and access to information by administering vitamin A capsules to toddlers. The method used is an analytical survey with a cross sectional approach. the research population is mothers who have toddlers aged 1-5 years. The Sampling Technique was purposive sampling with the number of samples were 98 respondents. Data collection was carried out using interviews and questionnaires. The data that has been collected is then processed and analyzed using the SPSS version 20 statistical program and analyzed using the chi-square test. Results: there is a relationship between mother's level of knowledge and giving vitamin A capsules to toddlers (p=0.000) and there is a relationship between mother's access to information and giving vitamin A capsules to toddlers (p=0.000). Conclusion: there is a relationship between knowledge level and mother's access to information by giving vitamin A capsules to toddlers.